Туристична інфраструктура Рожищенського району Волинської області як інструмент туристичної привабливості території - Чир, Надія Вікторівна; Качаровський, Роман Євгенович; Антипюк, Олена Володимирівна; Chyr, Nadiia V.; Kacharovskyi, Roman Ye.; Antypiuk, Olena V. (Сумський державний педагогічний університет імені А.С. Макаренка, 2019)
Досліджено питання туристичної привабливості Рожищенського району Волинської області. Здійснено системний аналіз наявного природно-рекреаційного потенціалу та істо-рико-культурної спадщини. Особлива увага акцентується на оцінці можливостей функціо-нування та розвитку туристичної інфраструктури Рожищенського району за окремими пі-дсистемами, що включають заклади розміщення, харчування, дозвілля та побутового обслу-говування, транспортної інфраструктури, зв’язку та інформаційного забезпечення. Визна-чено основні проблеми структурних елементів туристичної інфраструктури. Подано пропозиції першочергових заходів оптимізації туристичної інфраструктури як інструменту підвищення туристичної привабливості дестинації.

The Rozhysche district of the Volhyn region hasn’t known as a tourism destination among the Ukrainian tourists very well because of a lack of information about available resource potential, tourist attractions, the state of the tourist infrastructure and tourist products of the region. Therefore there is an urgent necessity to research these aspects. It could become an impulse in the activation the tourist flow, the lever of the formation of a competitive tourist product of regional and local significance. It also gives a great opportunity to increase the investment attractiveness of the territory, to solve partly the issue of employment of the population and essentially fill the budgets of all levels. The issue of tourist attraction of the Rozhysche district of the Volhyn region is investigated. The comprehensive evaluation of the tourist-recreational potential of the district has made. The main natural recreational tourist resources and the components of the historical and cultural heritage, which determine the tourist specialization of the studied area, have characterized. Balneological resources are represented by the deposits of sapropel, which makes it possible to develop sanatorium and spa treatment. An important structure-forming element of the natural resource potential are the water and forest recreational tourist resources. They could be used for the development of the various forms of ecological tourism. In the district function 11 objects of the natural reserve fund. The analysis of the current state and possibilities for the development of tourism infrastructure in separate subsystems has conducted: placement establishments, food establishments, leisure establishments and consumer service, transport infrastructure, communication and information services. The coefficient of security by the placement of the temporary accommodation is 0.49 un./km² and it is the average in the region. The restaurant economy is represented by 44 establishments. To optimize the subsystem «nutrition establishments» it’s necessary to follow the general tendency towards rebranding of non-competitive restaurant facilities in the alternative establishment. The subsystem "leisure facilities" is the weakest link in the tourist infrastructure on the explored territories.The main urgent problems in the Rozhysche district are providing the infrastructure improvement and the information management of the main attractive objects of historical and cultural heritage and of the natural reserve fund, which are the most popular among the tourists, the insufficient provision of the information about the tourist and recreational opportunities of the region. The main problems of the structural elements of the tourist infrastructure are identified. The suggestions of priority measures of optimization of tourist infrastructure as a tool for increasing the tourist attractiveness of the destination are presented.
The Tourist Infrastructure of Rozhysche District of the Volhyn Region as a Tool of Tourist Attractiveness of the Territory
Keywords: туристична інфраструктура; туристисчна привабливість; Волинська область; Рожищенський район; tourism; tourist infrastructure; tourist attractiveness; Rozhysche District; Volhyn Region